Variation in upper thermal tolerance among 19 species from temperate wetlands. (February 2021) - Katzenberger, Marco; Duarte, Helder; Relyea, Rick; Beltrán, Juan Francisco; Tejedo, Miguel
Abstract: Communities usually possess a multitude of interconnected trophic interactions within food webs. Their regulation generally depends on a balance between bottom-up and top-down effects. However, if sensitivity to temperature varies among species, rising temperatures may change trophic interactions via direct and indirect effects. We examined the critical thermal maximum (CTmax ) of 19 species from temperate wetlands (insect predators, amphibian larvae, zooplankton and amphipods) and determined if they vary in their sensitivity to warming temperatures. CTmax differed between the groups, with predatory insects having higher CTmax than amphibians (both herbivorous larval anurans and predatory larval salamanders), amphipods and zooplankton. In a scenario of global warming, these differences in thermal tolerance may affect top-down and bottom-up processes, particularly considering that insect predators are more likely to maintain or improve their performance at higher temperatures, which could lead to increased predation rates on the herbivores in the food web. Further studies are needed to understand how the energy flows through communities, how species' energy budgets may change and whether other physiological and behavioral responses (such as phenotypic plasticity and thermoregulation) can buffer or increase these changes in the top-down regulation of wetland food webs. Highlights: Critical thermal maxima (CTmax ) differs across species in temperate wetland communities from North America. Predatory insects are less susceptible to climate change than other organism within the same community. Variation in thermal limits amongst community components suggests that future climate change may affect community structure.